Anti-Infectivity against Herpes Simplex Virus and Selected Microbes and Anti-Inflammatory Activities of Compounds Isolated from Eucalyptus globulus Labill - Brezáni, Viliam; Leláková, Veronika; Hassan, Sherif T S; Berchová-Bímová, Kateřina; Nový, Pavel; Klouček, Pavel; Maršík, Petr; Dall'Acqua, Stefano; Hošek, Jan; Šmejkal, Karel (Viruses, 2018)
Herpes simplex virus (HSV) causes numerous mild-to-serious human diseases, including mucocutaneous herpes infections and life-threatening herpes encephalitis. Moreover, herpes viral lesions can be complicated by inflammation and secondary bacterial infections. The development of resistance to antiviral drugs along with the undesirable side effects of these drugs are relevant argue for the development of new anti-HSV drugs with diverse mechanisms of action. Eucalyptus extracts have been used for decades to combat various infectious diseases. We isolated and studied 12 pure compounds and one mixture of two constitutional isomers from the leaves and twigs of E. globulus. The structures were identified by spectroscopic methods (NMR, HR-MS, IR) and all of them were tested for antiherpetic activity against the replication of antigen types HSV-1 and HSV-2. Tereticornate A (12) (IC50: 0.96 μg/mL; selectivity index CC50/IC50: 218.8) showed the strongest activity in the anti-HSV-1 assay, even greater than acyclovir (IC50: 1.92 μg/mL; selectivity index CC50/IC50: 109.4), a standard antiviral drug. Cypellocarpin C (5) (EC50: 0.73 μg/mL; selectivity index CC50/EC50: 287.7) showed the most potent anti-HSV-2 activity, also more intensive than acyclovir (EC50: 1.75 μg/mL; selectivity index CC50/EC50: 120.0). The antimicrobial activity of the isolated compounds was also evaluated against the bacteria Staphylococcus aureus, Bacillus cereus, Escherichia coli, and Pseudomonas aeruginosa and the yeast Candida albicans. The anti-inflammatory potential was examined using LPS-stimulated THP-1-XBlue™-MD2-CD14 and THP-1 macrophages and focusing on the influences of the NF-κB/AP-1 activity and the secretion of pro-inflammatory cytokines IL-1β and TNF-α.
Keywords: Animals; Antiviral Agents; antiflogistika; IL-1β; antibacterial; Chlorocebus aethiops; NF-κB/AP-1; Antioxidants; buněčné linie; Cytokines; Transcription Factor AP-1; ROS; antivirové látky; Herpes Simplex; rostlinné extrakty; Vero Cells; cytokiny; antiherpetic; lidé; antiinfekční látky; Vero buňky; Anti-Bacterial Agents; Anti-Infective Agents; Reactive Oxygen Species; HSV-1; Cell Line; HSV-2; transkripční faktor AP-1; Eucalyptus; Anti-Inflammatory Agents; TNF-α; antioxidancia; Plant Extracts; reaktivní formy kyslíku; Cercopithecus aethiops; Cell Survival; NF-kappa B; zvířata; viabilita buněk; antibakteriální látky; anti-inflammatory; herpes simplex; Simplexvirus; Humans